Large-scale releases and establishment of wMel Wolbachia in Aedes aegypti mosquitoes throughout the Cities of Bello, Medellín and Itagüí, Colombia. - Iván Darío Velez; Alexander Uribe; Jovany Barajas; Sandra Uribe; Sandra Ángel; Juan David Suaza-Vasco; Maria Camila Mejia Torres; María Patricia Arbeláez; Eduardo Santacruz-Sanmartin; Lorena Duque; Luis Martínez; Tania Posada; et al. (Public Library of Science (PLoS), 2023)
Background The wMel strain of Wolbachia has been successfully introduced into Aedes aegypti mosquitoes and has been shown to reduce the transmission of dengue and other Aedes-borne viruses. Here we report the entomological results from phased, large-scale releases of Wolbachia infected Ae. aegypti mosquitoes throughout three contiguous cities located in the Aburrá Valley, Colombia. Methodology/principal findings Local wMel Wolbachia-infected Ae. aegypti mosquitoes were generated and then released in an initial release pilot area in 2015-2016, which resulted in the establishment of Wolbachia in the local mosquito populations. Subsequent large-scale releases, mainly involving vehicle-based releases of adult mosquitoes along publicly accessible roads and streets, were undertaken across 29 comunas throughout Bello, Medellín and Itagüí Colombia between 2017-2022. In 9 comunas these were supplemented by egg releases that were undertaken by staff or community members. By the most recent monitoring, Wolbachia was found to be stable and established at consistent levels in local mosquito populations (>60% prevalence) in the majority (67%) of areas. Conclusion These results, from the largest contiguous releases of wMel Wolbachia mosquitoes to date, highlight the operational feasibility of implementing the method in large urban settings. Based on results from previous studies, we expect that Wolbachia establishment will be sustained long term. Ongoing monitoring will confirm Wolbachia persistence in local mosquito populations and track its establishment in the remaining areas.